2022
DOI: 10.1371/journal.pone.0266199
|View full text |Cite
|
Sign up to set email alerts
|

Promoting and inhibiting: Corporate charitable donations and innovation investment under different motivation orientations——Evidence from Chinese listed companies

Abstract: Corporate charitable donations under different motivations will have different effects on innovation investment through different action paths, which provides a new perspective to solve the inconsistency of existing research results. Based on the resource-dependent and principal-agent theories, this paper compares and discusses the relationship between charitable donations and innovation investment under different motivations. Using 2008 ~2019 relevant data of listed companies as research samples, a mixed regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…By observing the variation of the coefficient between CG and GI it can be found that: The effect of CG on GI is as the saying "too much water drowned the miller" goes, i. e. too much CG will have a negative effect on GI. This result is consistent with the view of scholar Wang [ 12 ].CG can send positive signals to the outside world such as being financially sound or socially responsible, thus helping firms to obtain more external resource support [ 13 ]. However, if the level of CG input is low, it neither draws external attention to obtain external resource support nor takes up too much of the organization’s internal resources, so it does not have a substantial impact on the firm’s GI.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…By observing the variation of the coefficient between CG and GI it can be found that: The effect of CG on GI is as the saying "too much water drowned the miller" goes, i. e. too much CG will have a negative effect on GI. This result is consistent with the view of scholar Wang [ 12 ].CG can send positive signals to the outside world such as being financially sound or socially responsible, thus helping firms to obtain more external resource support [ 13 ]. However, if the level of CG input is low, it neither draws external attention to obtain external resource support nor takes up too much of the organization’s internal resources, so it does not have a substantial impact on the firm’s GI.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, Chinese government departments, as the allocators of some essential innovation resources, are an important source of external innovation resources for companies. CG can release to the government the corporate attitude of actively engaging in social responsibility and help enterprises gain more attention from the government, thus better-accessing resource support from the government (e.g., innovation project approval, innovation subsidies, policy support, and essential information resources), creating a resource effect that promotes corporate GI [ 9 , 12 , 14 ].…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, fewer analysts focus on the firm behaving irresponsibly. The lack of environmental information increases the cost of analysts to gather and process information, further reducing their attention toward the firm (Agyabeng-Mensah et al, 2020;Kang et al, 2010;Mutuc & Cabrilo, 2022) regarding the deterioration of corporate performance, which helps firms to stabilize and control existing business resources while preserving their financing environment (Chai et al, 2023;Wang et al, 2022).…”
Section: Financial Penalty Effect Of Ceirmentioning
confidence: 99%
“…In stark contrast to their neglect of environmental responsibility, many firms publicly prioritize their charitable donations (CD) and other philanthropic activities, often driven by cultural beliefs (Wang et al, 2022). CD are considered a significant aspect of corporate social responsibility, contributing to the regulation of wealth disparities, alleviation of social conflicts, and maintenance of social stability (Lu & Cheng, 2023).…”
Section: Introductionmentioning
confidence: 99%